Kredibilitas Informasi di Era Post-Truth Dikalahkan Kecepatan Informasi: Pengabaian Undang Undang Informasi dan Transaksi Elektronik - Meilya Syifa Aghniya Rahman; Silvi Puspita Dewi; Liza Shafira Ningtyas; Friska Lestari Samosir; Angelique Ezra Herviani; Zainal Abidin Achmad (Universitas Airlangga, 2022)
Many people choose social media as a source of information that is considered the fastest and most up-to-date without knowing its credibility for sure. In the post-truth era, social media has shifted the power of logic and facts, and often the information on it is considered true. This study aims to gain an understanding of the credibility of information uploaded by the Twitter account @AREAJULID. By using a virtual ethnography approach. This qualitative research explores the existence of a phenomenon of attraction between the influence of information speed and information credibility. The results of the search on the @AREAJULID account show that many followers of the account have the assumption that the speed of content uploaded by @AREAJULID makes it a trusted source of information. They even disseminate the information by retweeting and sharing the link on other social media channels such as Facebook, TikTok and WhatsApp. The followers' actions ignore the existence of the Electronic Information and Transaction Law. The post-truth era makes the @AREAJULID account a credible source of information precisely because of the speed of uploading and not because of the truth of the information. Keywords: post-truth, virtual ethnography, information credibility